Controlled drug release from pharmaceutical nanocarriers. (24th March 2015) - Lee, Jinhyun Hannah; Yeo, Yoon
Abstract: Nanocarriers providing spatiotemporal control of drug release contribute to reducing toxicity and improving therapeutic efficacy of a drug. On the other hand, nanocarriers face unique challenges in controlling drug release kinetics, due to the large surface area per volume ratio and the short diffusion distance. To develop nanocarriers with desirable release kinetics for target applications, it is important to understand the mechanisms by which a carrier retains and releases a drug, the effects of composition and morphology of the carrier on the drug release kinetics, and current techniques for preparation and modification of nanocarriers. This review provides an overview of drug release mechanisms and various nanocarriers with a specific emphasis on approaches to control the drug release kinetics. Graphical abstract: Highlights: Drug release mechanisms utilized in nanocarriers. Approaches to control drug release kinetics in various nanocarriers. Main achievements and limitations of each approach.